Credit Rating Inflation during the 2000s: Lessons from the U.S. State Governments - Kim, Sungchan; Park, Soyoung (International Journal of Economics and Financial Issues, 2016)
The recent subprime mortgage crisis in 2008 was considered as resulted partly from the credit rating inflation of subprime mortgage bonds. The credit rating market of state governments may face the same risk of credit rating inflation as that witnessed during the recent recession. In this paper, we attempt to examine whether the credit ratings of state governments are inflated, and whether they are accurately reflected in financial or economic conditions. By using a data set from 1999 to 2010, we find that some credit rating agencies don’t reflect financial or economic conditions of state governments appropriately and statistically, and we prove that some credit rating results are affected by characteristics other than financial or economic factors in boom years. Thus, in order to prevent the governmental bond markets from similar credit rating risks in 2008, it needs to investigate whether credit ratings of state governments are inflated. Keywords: Credit Rating Inflation; State Governments; Credit Rating Agency; Bond Ratings JEL Classifications: E5; G25